Database helps research planning on maize technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Maize Technology Development and Transfer: A GIS Application for Research Planning in Kenya Edited by R.M. Hassan, 1998, ISBN 0 85199 287 0, Publishing Division, CAB International Wallingford, Oxford, OX 10 8DE UK. Fax: +44 1491 833508 Email: